Exploring the association between the quality of HIV care in nursing homes and hospitalization - Olivieri-Mui, Brianne (J Healthc Qual, 2021)
Persons living with HIV/AIDS (PLWH) are living long enough to need age- and HIV-related nursing home (NH) care. NH quality of care has been associated with risk for hospitalization; but it is unknown if quality of HIV care in NHs affects hospitalization in this population. We assessed HIV care quality with four national measures adapted for the NH setting. We applied the measures to 2011–2013 Medicare claims linked to Minimum Dataset assessments of resident health, prescription dispensing data, and national reports of NH characteristics. Cox proportional hazards models calculated the risk of all-cause and HIV/AIDS-related hospitalization by HIV care compliance. We identified 1,246 PLWH in 201 NHs with 382 all-cause and 63 HIV/AIDS-related hospitalizations. NH HIV care compliance varied from 24.9% to 64.7%. After regression adjustment, we could detect no difference in all-cause or HIV/AIDS-related hospitalizations by NH HIV care compliance. We postulate that the lack of association may be due to inappropriate HIV care quality measures that do not accurately represent NHs ability to care for PLWH. There is urgent need to create valid NH HIV care quality measures.